Atividade in vitro e in vivo de peptídeos antimicrobianos análogos incorporados à nanopartículas de PLGA contra Staphylococcus aureus - Carmo, Bruno Amorim do (2023)
The emergence of multidrug-resistant microorganisms constitutes a serious global public health problem that limits therapeutic alternatives and underscores the urgent need for the discovery of new antimicrobial agents. The venom of the scorpion Tityus stigmurus is a rich source of biologically active components, including antimicrobial peptides with high therapeutic potential, such as Stigmurin. The structure of Stigmurin was used as a prototype for obtaining more potent molecules, with modifications made to its structure, resulting in 31 analogs (patent BR102015029044-6). In this study, nuclear magnetic resonance (NMR) was used to characterize, stability was investigated, and the in vitro and in vivo antibacterial action of two analog peptides, named StigA25 and StigA31, was evaluated. In addition to the notable antimicrobial activity previously described in another study, the peptides StigA25 and StigA31 exhibited concentration-dependent hemolytic activity compared to the prototype peptide. In order to reduce cytotoxicity, enhance stability, and maximize the therapeutic efficiency of these peptides, the effect of associating these bioactive components with poly(lactic-co-glycolic acid) (PLGA) nanoparticles was investigated. StigA25 and StigA31 showed a predominant α-helical conformation by NMR, with high structural stability under different temperature and pH conditions, as well as in the presence of salts by circular dichroism. The association of these peptides with PLGA nanoparticles enabled the formation of a stable nanosystem with a high peptide incorporation index, antimicrobial activity equivalent to that of free peptides, and a significant reduction in toxicity. Scanning and transmission electron microscopy demonstrated that both free and nanoparticulated peptides act by disrupting the bacterial cell membrane. In both the mouse sepsis model and the S. aureus infection model in Galleria mellonella, both free and nanoparticulated peptides were effective in controlling the infectious process. Therefore, this study reveals the high therapeutic potential of StigA25 and StigA31 associated with a PLGA nanosystem, indicating the use of this nanocarrier as a promising tool for the therapeutic application of these molecules in the development of new anti-infective agents.